Pre-operative urodynamic studies : is there value in predicting post-operative stress urinary incontinence in women undergoing prolapse surgery - Janse van Rensburg, Karina (Stellenbosch : Stellenbosch University, 2013)
Thesis (MMed)-- Stellenbosch University, 2013.